1997
DOI: 10.1074/jbc.272.20.12897
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Induces Mitogen-activated Protein Kinase- dependent Proliferation of C3H10T1/2 Cells

Abstract: Leptin, secreted by adipocytes, regulates satiety and energy expenditure. Several forms of leptin receptors produced by alternative mRNA splicing are found in many tissues, including the hypothalamus, liver, lung, kidney, hematopoietic cells, and gonads, suggesting that leptin exerts effects in these tissues. In accordance with the distribution of leptin receptors, there is accumulating evidence that leptin plays various roles in reproduction, hematopoiesis, and the immune systems in addition to the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
2
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 51 publications
(39 reference statements)
10
117
2
5
Order By: Relevance
“…Several in vitro studies indicate that stromal cells are responsive to leptin, which increases proliferation, differentiation to osteoblastic lineage and the number of mineralized nodules (Takahashi et al 1997, Thomas et al 1999, Reseland et al 2001, but inhibits differentiation to adipocytes (Thomas et al 1999, Hess et al 2005. These observations suggest that leptin may participate in the regulation of bone mass, but the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 90%
“…Several in vitro studies indicate that stromal cells are responsive to leptin, which increases proliferation, differentiation to osteoblastic lineage and the number of mineralized nodules (Takahashi et al 1997, Thomas et al 1999, Reseland et al 2001, but inhibits differentiation to adipocytes (Thomas et al 1999, Hess et al 2005. These observations suggest that leptin may participate in the regulation of bone mass, but the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 90%
“…The effect of ERK1/2 signaling on TIMP-1 promoter activity was specific, because it was blocked by the ERK1/2 inhibitor PD098059, but not by SB203580 or overexpressing dominant negative p38 mutants. ERK1/2 activation by leptin or its receptors has been reported in a number of cell systems (32)(33)(34)(35)64). In COS and Chinese hamster ovary cells transfected with the leptin receptors, ERK1/2 can be activated via two pathways.…”
Section: Timp-1 Induction By Leptinmentioning
confidence: 99%
“…But leptin can also use other signaling cascades via JAK activation. Among these are p38 (31), extracellular signal-regulated kinase (ERK1/2) (2,(31)(32)(33)(34)(35)(36), and c-Jun terminal/stressactivated protein kinases (37) of the mitogen-activated protein kinase (MAPK) family members. Furthermore, leptin was found to generate increased amounts of H 2 O 2 in isolated vascular endothelial cells in association with atherogenic processes (37,38).…”
mentioning
confidence: 99%
“…This finding, in combination with the previously mentioned observation that insulin stimulates leptin secretion, suggests the existence of a negative feedback loop between leptin and insulin. Second, one study suggested a decrease in insulin receptor substrate-1 (IRS-1) phosphorylation as well as modulation of downstream effectors of insulin action and up-regulation of gluconeogenesis in hepatocytes exposed to leptin in vitro [88], although other studies have produced conflicting results [89,90]. Finally, leptin has been recently shown to stimulate haematopoiesis in vitro [91,92] and has also been found in human fetuses, where it may be involved in the regulation of fetal haematopoiesis [57, 93,94].…”
Section: Leptin Actions In the Central Nervous System And Peripheral mentioning
confidence: 99%